Aqueous Extract of Moringa oleifera Exhibit Potential Anticancer Activity and can be Used as a Possible Cancer Therapeutic Agent: A Study Involving In Vitro and In Vivo Approach. (2nd January 2021) - Barhoi, Dharmeswar; Upadhaya, Puja; Barbhuiya, Sweety Nath; Giri, Anirudha; Giri, Sarbani
Abstract: Objectives: New cases of cancers are increasing at an alarming rate globally. It has been hypothesized that modern cancer treatment is associated with lots of side effects and thus evoking the need to develop safer treatment measures. Thus, the present study was undertaken to evaluate the anti-carcinogenic potential of a highly nutricious plant " Moringa oleifera" (MO) in vitro and in vivo . Methods: GC-MS analysis of aqueous extract of Moringa oleifera (AEMO) was employed to identify the bioactive compound present. Anti-tumor activity of AEMO was assessed in EAC (Ehrlich acites carcinoma) induced solid tumor bearing mice by analyzing tumor weight (TW) and Tumor volume (TV). To assess AEMO induced cytotoxicity, EAC and HEp-2 (Human laryngeal carcinoma) cells were treated with AEMO (0.05, 0.1, 0.25, 0.5 and 1 mg/ml) for both 48 h and 72 h and trypan blue, MTT and LDH released assay was done. Further, cell cycle assay and apoptosis assay was done in EAC cells to understand the mechanism of AEMO induced tumor regression. Results: GC-MS analysis revealed the presence of quinic acid, octadecanoic acid, hexadecanoic acid (palmitic acid), α-tocopherol (Vitamin-E) and ɣ-sitosterol as major bioactive compounds. AEMO administration reduced the TV and TW of tumor-bearing mice and increases the life span. Side effect analysis showed that AEMO treatment did not induce significant alterations of liver and kidney function and hematological parameters. Further, in vitro cytotoxicity assays revealed that AEMO treatment induced dose and time-dependent toxicity in both the cell lines tested. Flow cytometric analysis confirmed significant induction of apoptotic cells by changing the mitochondrial membrane potential in EAC cell line. Conclusion: The results of the present study suggest that AEMO has immense potential to inhibit the tumor progression without affecting the normal physiology and functioning of the body and thus can be used as a cancer therapeutic agent.